Looking beyond the obvious: Uncovering the features of natural resource conflicts in Uganda - Nkonya, Ephraim M.; Markelova, Helen (International Food Policy Research Institute, 2009)
Disputes over land, water, forests, rangelands, and other resources, both privately and commonly-held, are omnipresent across Africa and increasing in number due to the socioeconomic and environmental changes happening on micro- and macro-levels. Communities in Africa have a variety of mechanisms rooted in customary and statutory institutions to deal with disputes. This paper uses community-level survey data from Uganda to investigate the determinants of natural resource conflicts and the type of institutions people turn to for conflict resolution. The findings identify four primary types of conflicts (over private land boundaries, common-pool resources other than water, water resources, and conflicts over other resources) and reveal that several factors such as agroecological potential, poverty level, population density, and proximity to roads and markets affect the likelihood of a resource-related conflict. The results also show that even though most people turn to the local government (a formal institution) for arbitration, customary institutions still play an important role in conflict management, especially for the poorer communities where formal institutions are weak. The type of conflict also matters for the type of institution chosen to resolve it with the conflicts over commons being mediated through customary institutions, while all the others are usually channeled though the local government. The findings point to the importance of both customary and formal institutions for conflict resolution options in Uganda, highlighting the need to examine their potential complementarities.